The flow of homicide cases through the criminal justice funnel - Liem, Marieke (Routledge handbook of homicide studies, 2024)
The funnel model serves as an effective tool for analyzing the processing of homicides across different jurisdictions and over time. The first dimension emphasizes the need for an accurate representation of the legal frameworks, decision-making procedures, and stages in a particular jurisdiction. The second dimension involves obtaining precise estimates of the probabilities of a particular outcome for all cases that enter a specific stage of the process. This includes determining the likelihood of a case transitioning to the next stage of the funnel. The third dimension pertains to comprehending the time that cases spend in a particular stage and the investigative, administrative, and judicial procedures that lead to the next decision point. The fourth dimension aims to comprehensively capture information on the legal and extra-legal factors and case characteristics that may affect the outcome of a case at a given decision point. At each of these judicial stages, selectivity takes place. Homicide cases may drop out for several legal reasons, for example, or may drop out when they remain uncleared in the absence of sufficient evidence, there may be no prosecution when the suspect is dead, or no sentencing when the suspect is not criminally responsible.